FLOUTING MAXIMS PERFORMED BY THE CHARACTERS IN JACKIE MOVIE: A PRAGMATICS ANALYSIS - Jiwalno, Jiwalno; Valiantien, Nita Maya; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
The objectives of this research are to find the kinds of flouting maxim in Jackie movie performed by the characters and to find the motivation of the characters in flouting the maxim. This research used a qualitative content analysis approach. The data source of this research was the script of Jackie movie. The data were taken from the dialogues and utterances of the characters that are correlated with flouting maxim. Through the findings of the analysis, there were 24 dialogues containing the flouting maxim. Those data consisted of four kinds of flouting maxim, namely flouting maxim of quality, flouting maxim of quantity, flouting maxim of relation, and flouting maxim of manner. In flouting the maxim, it was found that the characters had an underlying motivation. From four types of motivation which were competitive, convivial, collaborative, and conflictive, the characters within the movie flouted the maxim with only two types of the motivation, namely competitive and collaborative.